COMBINATION TENDON AND NERVE GLIDING EXERCISE WITH NEURODYNAMIC MOBILIZATION TO IMPROVE HAND FUNCTION IN CARPAL TUNNEL SYNDROME PATIENT: A CASE REPORT - Sekaringtyas, Dyah; Susilo, Taufik Eko; Prihati, Eko (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy of the upper extremity caused by compression of the median nerve with an overall prevalence in the general population of 5.3% for women and 2.1% for men. In general, CTS will cause pain, neurological symptoms, and decreased functional ability and can interfere with daily activities. Treatment of carpal tunnel syndrome (CTS) can be done by giving a physiotherapy program, one of which is exercise. The purpose of this study was to determine the effectiveness of the combination of tendon and nerve gliding exercise with neurodynamic mobilization on increasing functional activity in patients with Carpal Tunnel Syndrome (CTS). Case Presentation: A 19-year-old woman came with a diagnosis of Carpal Tunnel Syndrome Dextra. She had a tingling sensation in his 1,2,3 and 4th half finger with carpal compression and a positive Phalen test. The patient was given a combination of tendon and nerve gliding exercise with neurodynamic mobilization for 6 weeks face-to-face and was evaluated. Management & Outcome: The patient showed good adherence to the program and achieved the desired goal within 6 weeks of therapy. The patient showed improvement (in pain, range of motion, and hand function. Tendon and nerve gliding exercise combined with neurodynamic mobilization was effective in improving clinical symptoms in patients with CTS. Discussion: Several recent pieces of literature state nerve and tendon gliding exercise as an alternative intervention in conservative management of CTS. Nerve and tendon gliding exercise is a joint and tendon mobilization exercise program that can be applied by performing several movements of the hands and wrists. This case report combines neurodynamic mobilization. This Exercise Program was carried out for 6 sessions and after 6 weeks of close monitoring and guidance of a combined training program. Overall, the results of this case report for CTS-related disorders and clinical symptoms showed significant results for improving hand function in CTS patients. Conclusions: A combination of tendon and nerve gliding exercise with neurodynamic mobilization is effective for improving hand function in CTS patients.